Hedonic price comparison of fixed broadband services: a Hungarian case study - Zoltan Papai; Aliz McLean; Tamas Bukur (International Telecommunications Society (ITS), 2023)
This study examines the changes in consumer prices within the fixed broadband market in Hungary between 2020 and 2022, a period marked by unprecedented market consolidation. Leveraging a hedonic price regression methodology, we inspect price changes in the context of internet service provider (ISP) differences, inflation, and various service features offered in broadband plans. The hedonic method allows for quality-adjusted price tracking over time, in addition to offering insights into the intrinsic value placed on various plan characteristics by consumers. The overall hedonic price index calculated in this study shows a 9.9% decrease in quality-adjusted prices over two years, suggesting enhanced value-for-money for customers. This is striking next to over 20% inflation, as shown by the consumer price index. Moreover, our results show that there are no significant price differences between the wellestablished ISPs, while the challenger third player has continued to exert strong competitive pressure by applying significantly lower quality-adjusted prices. However, given this player's involvement in the recent market consolidation, we anticipate that their pricing will align more closely with other ISPs' in the future. The estimated intrinsic prices of the various fixed broadband plan characteristics are consistent with previous literature. The study underlines the utility of the hedonic methodology in providing nuanced insights into ISP pricing behaviour and fixed retail telecom market dynamics. The study opens up potential areas for future research, such as extending the analysis to television and voice telephony and monitoring future trends in light of the recent changes in market structure.
Keywords: 330; hedonic regression; telecommunications; fixed broadband; pricing; Hungary